The water quality index of the stream Cacau sub-basin, Amazon Portal Imperatriz -MA (Research, Society and Development, 2021)
The objective of the work was to assess the water quality of the stream Cacau sub-basin over the years in the urban area of the city of Imperatriz-MA (Amazon portal), aiming to subsidize instruments for the management of urban water resources. In this study, aspects of human interference in the aquatic ecosystem were considered. The interferences in the water quality were evaluated by the following variables: pH, Redox potential, Chlorides, Alkalinity, Acidity, Dissolved oxygen, Total nitrogen, Total phosphorus, Temperature, Electrical conductivity, Turbidity, total solids, Particulate matter in suspension, Total and coliforms Thermotolerant coliforms, with the parameters created a database on the real situation of the water body. After assessing the physical and chemical characteristics of the stream waters, the Water Quality Index was calculated using the Basic method (IQAb) and the Person correlation coefficient. Riacho Cacau obtained water quality indexes ranging from good to excellent in the years 2015-2016 when compared to the values ​​2018-2019, in which 50% of the samples obtained Good IQA, 25% Excellent IQA and 25% Pleasant.